Our own - other - alien in educational practice. The school environment in the face of national and religious diversity and the sense of security - Adam Bobryk (Studia z Teorii Wychowania)
The article analyses the functioning of the school environment in terms of perceiving students in the categories of "our own", "other", "foreign", which is related to their national and religious affiliation, citizenship and foreigner status. Classification into individual categories on the "our own" - "foreign" axis is based on various premises and does not apply to all minority communities to the same extent. Roma people, Muslims and foreigners, especially refugees, are particularly susceptible to classification into "foreign" or "other" groups. Currently, foreign students in Poland constitute 6.71% of the total and their share is constantly increasing. The threat to the sense of security carries a number of negative consequences in terms of education, upbringing and development. Therefore, various initiatives should be undertaken in the school environment to promote mutual understanding, understanding differences and integration of communities.